Antimicrobial activity and synergic effect of cinnamomum burmannii’s essential oil & its isolated compound (Cinnamaldehyde) - Awang, Anis Fadhlina Izyani; Darnis, Deny Susanti; Bakhtiar, M. Taher (2013)
Cinnamomum burmannii is one of the species in Cinnamomum genus and belongs to the Lauraceae family. It has a common name called Indonesian Cassia. The aims of the present study were to investigate the antimicrobial activity of C. burmannii’s essential oil and its major compound, cinnamaldehyde against selected microorganisms. This study also aimed to study the synergic effect of C. burmannii’s essential oil as well as cinnamaldehyde upon combining with the current antibiotics. Steam distillation was used for extraction of the essential oil. The isolation of cinnamaldehyde from the essential oil was conducted using column chromatography and the characterization of the compound was analyzed using spectroscopic techniques. The antimicrobial assay was done using micro-dilution methods against three microorganisms in triplicate. The MIC value of essential oil and cinnamaldehyde was found to be 0.33 mg/mL against E. coli, S. aureus and C. albicans. The FIC index upon combination was in the range of 1 < FIC ≤2 which was evaluated as indifference effect. The present study was able to clarify the crucial role of cinnamaldehyde as a potent antimicrobial compound of the C. burmannii’s essential oil.